Renewable resilience in conflict: lessons learned from Syria’s solar-powered electric health vehicles - Ahmad A. Alnasser; Mohammad Darwish; Ahmed Aldbis; Camila Polinori; Camila Polinori; Shatha Elnakib; Saverio Bellizzi; Daher Zedan; Bara Zuhaili (Frontiers in Public Health)
The Syrian Civil War has resulted in significant devastation, including widespread displacement of millions and extensive damage to infrastructure, particularly healthcare infrastructure. Attacks on healthcare facilities have been frequent, leading to a drastic reduction in available medical services and the exodus of healthcare workers. The resulting impact on civilians, compounded by energy shortages, has been severe, limiting access to essential services. In response to these challenges, the Union of Syrian Medical Relief Organizations (UOSSM) has introduced the solar-powered electric vehicles for healthcare transportation in Northwest Syria. This development is a significant step toward sustainable energy solutions in conflict zones, providing a reliable source of power for essential services such as healthcare delivery. In this paper, we document this experience which underscores the importance of local involvement and partnerships in implementing such solutions, as well as the need for broader research and education initiatives to ensure the long-term viability of renewable energy systems. These initiatives allow for a sustainable future solution while enabling local actors to participate in their development and maintenance. By prioritizing sustainability and autonomy, initiatives like UOSSM’s solar-powered electric car demonstrate the potential for innovative responses to complex humanitarian crises around the world, following Syria’s example.